2022
DOI: 10.3389/fneur.2022.869107
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Monitoring for Delayed Cerebral Ischemia in Subarachnoid Hemorrhage: A Mini Review

Abstract: Aneurysmal subarachnoid hemorrhage is a disease with high mortality and morbidity due in large part to delayed effects of the hemorrhage, including vasospasm, and delayed cerebral ischemia. These two are now recognized as overlapping yet distinct entities, and supportive therapies for delayed cerebral ischemia are predicated on identifying DCI as quickly as possible. The purpose of this overview is to highlight diagnostic tools that are being used in the identification of DCI in the neurocritical care settings. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…A detailed review of invasive neuromonitoring modalities and their use in cerebrovascular diseases is beyond the scope of this review and can be found elsewhere. 58,59…”
Section: Neuromonitoring To Direct Precision Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…A detailed review of invasive neuromonitoring modalities and their use in cerebrovascular diseases is beyond the scope of this review and can be found elsewhere. 58,59…”
Section: Neuromonitoring To Direct Precision Medicinementioning
confidence: 99%
“…A detailed review of invasive neuromonitoring modalities and their use in cerebrovascular diseases is beyond the scope of this review and can be found elsewhere. 58,59 Integration of Physiologic and Clinical Variables Most physiologic monitoring data are automatically captured and archived in the electronic health record as numeric values averaged over a set period. High-resolution waveforms are generally excluded from routine storage and only displayed at the bedside.…”
Section: Invasive Neuromonitoringmentioning
confidence: 99%